Biochemical study of attached macroalgae from the Madeira Archipelago and beach-cast macroalgae from the Canary Islands: multivariate analysis to determine bioresource potential - Nunes, Nuno (2020)
Fifteen attached macroalgae from the Madeira Archipelago, comprising three green, three red and nine brown algal species, as well as two beach-cast macroalgal samples, collected along the north shore of Gran Canaria, were assessed for their biochemical properties. The anal ysis included the determination of total minerals, total carbohydrates, protein, lipids, chlorophyll a, total carote noids, total phenolic content, fucoxanthin and phycobilins (allophycocyanin, phycocyanin and phycoerythrin). The results showed a high variability of biochemical composi tion, allowing for the targetting of specific bioresources for particular purposes, including functional foods. This work provides the foundation for a biorefinery strategy implementation plan, for which specific macroalgae may be tar geted for valuable and beneficial compounds